Penguatan Profil Pelajar Pancasila dalam Mengembangkan Kreativitas Peserta Didik di SDIT Ummu Fathimah Kota Bengkulu - Pransista, Nadia; Radhiatun Mardhia, Annisa; Wahyurini, Ernanti; Asvio, Nova (JPT : Jurnal Pendidikan Tematik, 2024)
The Pancasila student profile has six dimensions including: 1) faithful, devoted to God Almighty, and noble, 2) independent, 3) mutual cooperation, 4) global diversity, 5) critical reasoning, and 6) creative. This research was conducted using a type of case study research focusing on a single object, such as a program, an individual, a group, an institution or institution, an organization. Based on the results of research and interviews by several sources conducted in class IV at SDIT Ummu Fatimah Bengkulu City in October to November 2023, namely at SDIT Ummu Fatimah Bnegkulu City has used the latest curriculum, namely the independent curriculum since September 2022, at SDIT Ummu Fatimah has also implemented the Pancasila student profile and strengthening the dimensions of the Pancasila student profile. In strengthening the dimensions of the Pancasila student profile, educators explain the material with the P5 theme. To produce a project, educators choose the theme of a sustainable lifestyle by utilizing waste, and developed according to the creativity of students. Therefore, based on the results of research and interviews, researchers are interested in conducting research on strengthening the profile of Pancasila students in developing students' creativity at SDIT Ummu Fatimah Bengkulu City.